2009
DOI: 10.1074/jbc.m807579200
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-neurodegeneration Drug Clioquinol Inhibits the Aging-associated Protein CLK-1

Abstract: The development of neurodegenerative diseases such as Alzheimer, Parkinson, and Huntington disease is strongly agedependent. Discovering drugs that act on the high rate of aging in older individuals could be a means of combating these diseases. Reduction of the activity of the mitochondrial enzyme CLK-1 (also known as COQ7) slows down aging in Caenorhabditis elegans and in mice. Clioquinol is a metal chelator that has beneficial effects in several cellular and animal models of neurodegenerative diseases as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…Treatment of C . elegans with clioquinol mimics several aspects of the clk-1 phenotype, in particular the inability to grow on bacteria that are deficient in UQ biosynthesis, yet does not significantly prevent UQ synthesis, suggesting a possible function of CLK-1 in UQ transport 16 .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Treatment of C . elegans with clioquinol mimics several aspects of the clk-1 phenotype, in particular the inability to grow on bacteria that are deficient in UQ biosynthesis, yet does not significantly prevent UQ synthesis, suggesting a possible function of CLK-1 in UQ transport 16 .…”
Section: Introductionmentioning
confidence: 94%
“…Another observation suggesting an alternative function for CLK-1 comes from study of the anti-neurodegenerative divalent metal chelator clioquinol 16 . Clioquinol inhibits mammalian CLK-1 (MCLK1 in mice and COQ7 in humans) in cultured cells, presumably by preventing the binding of the two prosthetic iron atoms that are necessary for the catalytic function of CLK-1 17 .…”
Section: Introductionmentioning
confidence: 99%
“…It was rediscovered in 2000s to be a drug candidate for Alzheimer's disease since treatment with CQ rapidly reduced plaques in Tg2576 transgenic mice (Cherny et al, 2001). It was later found that CQ also showed beneficial effects in cellular and animal models of PD (Lei et al, 2012;Kaur et al, 2003Kaur et al, , 2009Tardiff et al, 2012), Huntington's disease (HD) (Nguyen et al, 2005), cancer (Chen et al, 2007;Ding et al, 2008;Yu et al, 2009), and it can protect against aging sequelae (Wang et al, 2009;Adlard et al, 2014a). It also was tested in a Phase 2 clinical trial in AD, which reported that it was well tolerated and that treatment slowed cognitive deterioration (Ritchie et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, clioquinol gained a renewed interest due to the observations of its neuroprotective activity contrary to the previous claims regarding SMON cases. Clioquinol has antimicrobial activity against C. albicans, E. coli, S. aureus and S. Epidermidis [11,23,24]. Clioquinol is a chelator of copper, zinc, and iron.…”
Section: Discussionmentioning
confidence: 99%